RETRACTED: Road traffic incidents involving pedestrians in areas with limited visibility - Turdibekov Saloxiddin; Isoxanov Utkir; Shermatov Shamshir; Abdusamatov Erkinjon; Usmanova Maxira (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001